Novel Copper Desorption from a Functionalized Fly Ash Adsorbent Using 1,1,1-Trifluoro-2,4-Pentanodione in Ionic Liquid [Bmim][Tf2n]: Experimental and Quantum Chemistry Calculations - Pizarro-Konczak, J; Romero-Figueroa, J; Castillo-Castillo, X; Quijada-Maldonado, E; Olea-Chandia, F; Ulloa-Ferrari, L (Elsevier B.V., 2023)
In the context of the current environmental issues and the need to consolidate effective efforts according to the criteria of a circular economy, adsorption of copper from water with functionalized materials has shown high performance at low cost. However, desorption requires high amounts of acid and base to regenerate the functionalized material. In order to overcome this drawback, this work proposes an alternative desorbing phase based on a specific extractant for copper 1,1,1-trifluoro-2,4-pentanodione (TFA) dissolved in the ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide. In this way, adsorption experiments were carried out using adsorbent fly ash, modified with a mesoporous siliceous material, and functionalized with 3-aminopropyl-triethoxysilane (APS). Under the operating conditions of this study, the best desorption performance was achieved using the lowest functionalization percentage of the absorbent material. The desorption percentage reached 45% after 200 min of contact with a stirred solution of TFA 0.2 [M] in IL. This percentage can be increased to around 70% through a second contact with fresh desorbing phase. Meanwhile, the conventional desorption technique with nitric acid showed faster kinetics and a slightly higher desorption percentage close to 50%. In turn, the final pH of the adsorbent slightly decreased when the proposed desorbing phase was used, representing an advantage over the use of acid. Additionally, it was possible to decrease the amount of desorbing phase allowing the concentration of copper. The COSMO-RS calculations indicate that a more hydrophobic IL could increase desorption percentage. © 2023 The Author(s)